The relevance of social sciences, in education and health research, from the qualitative perspective - Núñez Rivas, Hilda P. (2018)
In the framework of Habermas' theory of knowledge constitutive interests, the health sciences have not been formally positioned in it to explain, understand and transform their objects or phenomena of study in depth. The scientific societies of health sciences have analyzed these sciences and carried out the training and continuing education of their personnel using the traditional positivist scientific method and have relegated the use of other scientific methods "naturalistic-qualitative" contributed by the social sciences. The purpose of this essay is to outline four theoretical-methodological aspects that justify the use of a mixed methodology and provide research experiences with these methods. It is concluded that it is not the use of a particular technique that defines a researcher as positivist or interpretative or sociocritical, but it is necessary to understand the existence of a correlation between the paradigm and the quantitative and qualitative research methods and their use in a mixed methodology, in order to study reality in a holistic way. It is not productive to give preference to only one of these styles of thought and to exclude the potential of other ones. Consequently, the essential and necessary thing is to examine reality in its entirety, with pluralistic methodologies to promote its change towards conditions of greater equity and social justice.